Concentração plasmática e analgesia associadas a fentanila intravenosa ou peridural em cadelas submetidas a ovariohisterectomia - Pereira, Carlos Eduardo Mayor [UNIFESP] (2017)
Introduction: Pharmacokinetics and adverse effects are important factors in opioid investigation. Research has demonstrated the difference in plasma concentration of fentanyl over time, initially presenting its analgesic effect and, subsequently, adverse effects. Thus, the replacement of the venous to epidural route of administration may present a difference in the pharmacokinetics of the medication, and may contribute to a reduction of the side effects. The objective of this study was to evaluate the plasma concentration, analgesia and adverse effects on intra and postoperative fentanyl administered by the venous or epidural route in females dogs submitted to ovariohysterectomy. Method: After approval of the Ethics Committee for the Use of Animals of the Institution. Twenty animals were randomized into 2 groups. Group (FP) (n = 10) was administered fentanyl 8μg.kg-1 in epidural route and 0.9% sodium chloride intravenously. Group (FV) (n = 10) intravenous fentanyl 8 μg.kg-1 and 0.9% sodium chloride were injected in epidural route. The animals were submitted to ovariohysterectomy and evaluated for a period of 120 minutes in relation to plasma fentanyl concentration and clinical parameters: heart rate, respiratory rate and body temperature. Results: There was a significant difference between the two groups. In the FP group the plasma concentration was lower at the beginning and higher at the end of the experiment. In contrast, the FV group presented a more pronounced fall in plasma concentration. Both groups presented adequate intra and postoperative analgesia, however, the body temperature of the animals of the FP group presented a significant decrease in relation to the Animals of the FV group. Conclusion: Under the conditions of this study, intravenous and epidural fentanyl presented intra and postoperative analgesic similarity with no difference for respiratory adverse events. The epidural fentanyl promoted a bigger decrease in temperature, alerting to the fact of the importance of measures for temperature maintenance in the intraoperative period.